2010
DOI: 10.5851/kosfa.2010.30.4.641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Activities of Ethanol Extracted Garlic and Onion as Affected by Pre-heating for the Application of Meat Products

Abstract: The objective of this study was to evaluate the pre-heating treatment effects on the antioxidant properties of ethanolic garlic and onion extracts. Garlic and onion with or without heating (100 o C, 30 min) were extracted with ethanol, and the total phenolic content, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging ability, iron chelating ability, reducing power, and antioxidant activity in a linoleic acid emulsion system were evaluated. Garlic (41%) had a higher drying yield than onion (11%). Regardles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…In contrast to red onion (4.4 ±0.52 mg CE/100g DM), garlic has a higher value of condensed tannins (6.8 ±0.34mg CE /100g DM). Our percentage yield of garlic extract was higher than previous studies findings (Park and Chin, 2010), (Ali and Mohsen Sabri, 2014) and (Bhanot and Shri, 2010) which were 2.46%, 6% and 7% respectively. According to Kallel et al, (2014), aqueous garlic extract has a higher percentage of extract yield (26.5%) than ethanolic and methanolic garlic extracts, which were 4% and 7% respectively.…”
Section: Phytochemical Analysiscontrasting
confidence: 80%
“…In contrast to red onion (4.4 ±0.52 mg CE/100g DM), garlic has a higher value of condensed tannins (6.8 ±0.34mg CE /100g DM). Our percentage yield of garlic extract was higher than previous studies findings (Park and Chin, 2010), (Ali and Mohsen Sabri, 2014) and (Bhanot and Shri, 2010) which were 2.46%, 6% and 7% respectively. According to Kallel et al, (2014), aqueous garlic extract has a higher percentage of extract yield (26.5%) than ethanolic and methanolic garlic extracts, which were 4% and 7% respectively.…”
Section: Phytochemical Analysiscontrasting
confidence: 80%
“…Both ethanol extracted garlic and onion powder inhibited the formation of hydroxylperoxide in a linoleic acid emulsion system. Antioxidative activities of garlic and onion extracts were not affected by preheating (Park and Chin, 2010b). Min et al (2010) measured antioxidant activities of garlic stem and red cabbage and reported that antioxidant activities of ethanol extracts of garlic stem were lower than those of red cabbage.…”
Section: Natural Antioxidantsmentioning
confidence: 99%